2007
DOI: 10.1007/s10641-007-9288-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability of behavioral syndromes but plasticity in individual behavior: consequences for rockfish stock enhancement

Abstract: This study investigated behavioral syndromes, which are defined as correlations between behaviors. Behavioral syndromes can lead to the unintentional alteration of a wide range of behavioral traits of hatchery fish if unintentional selection on one behavior leads to selection on a correlated behavior. Specifically, this study used brown rockfish, Sebastes auriculatus, to test the hypothesis that a fish that feeds at high rates in the absence of a predator also takes more risks when a predator is present, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…To the best of our knowledge, only 1 other study shows evidence of 'personality' in marine fish, having demonstrated consistent individual differences in behaviour, and correlations among behavioural traits, in 2 tropical species of damselfish from a genus that differs from the present study . Although Lee & Bereijikian (2008) found evidence for correlations between behavioural traits at a given point in time, they did not find within-individual consistency. Snekser et al (2009) observed consistency over time for several behaviours when fish remained on a single type of territory, but not when they moved across territory types (artificial versus natural).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To the best of our knowledge, only 1 other study shows evidence of 'personality' in marine fish, having demonstrated consistent individual differences in behaviour, and correlations among behavioural traits, in 2 tropical species of damselfish from a genus that differs from the present study . Although Lee & Bereijikian (2008) found evidence for correlations between behavioural traits at a given point in time, they did not find within-individual consistency. Snekser et al (2009) observed consistency over time for several behaviours when fish remained on a single type of territory, but not when they moved across territory types (artificial versus natural).…”
Section: Discussionmentioning
confidence: 70%
“…Although there is evidence of personality in a wide variety of animal taxa, including numerous freshwater fish species (Sih et al 2004, Reale et al 2007, there seems to be very little evidence for this phenomenon in marine fish with the exception of 3 studies: 1 study on stability of behavioural syndromes in rockfish (Lee & Bereijikian 2008), 1 study on behavioural correlations in Caribbean damselfish (Snekser et al 2009) and 1 study showing personality in 2 species of tropical damselfish . Given the rich taxonomic, social and competitive environments of temperate marine fish communities relative to temperate freshwater fish assemblages, we might expect marine fish to exhibit greater behavioural flexibility and greater differences in behaviour among species that serve to reduce competition and predation and allow persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Danio rerio (Hamilton 1822) (Moretz et al 2007) and Poecilia reticulata Peters 1859 (Harris et al , 2010), and marine fishes, e.g. Sebastes auriculatus Girard 1854 (Lee & Bereijikian, 2008) and Parma microlepis Günther 1862 (Eriksson et al , 2010). Repeatability values were high for a number of behaviours, suggesting that individuals behave similarly over time in their levels of activity, foraging, shoaling and predator inspection.…”
Section: Discussionmentioning
confidence: 99%
“…When measured 10 days later, the correlations were similar. These temporally stable correlations among behavior measures were therefore construed as 'behavioral syndromes' (Lee & Bereijikian, 2008). But the crucial point is that the individuals' behavior was not consistent.…”
Section: Meta-theoretical and Methodological Concepts Underlying 'Behmentioning
confidence: 99%